((-8)x)+(9x)-21=(-12)-16

Simple and best practice solution for ((-8)x)+(9x)-21=(-12)-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((-8)x)+(9x)-21=(-12)-16 equation:


Simplifying
((-8) * x) + (9x) + -21 = (-12) + -16

Reorder the terms:
-21 + (-8x) + (9x) = (-12) + -16

Combine like terms: (-8x) + (9x) = 1x
-21 + 1x = (-12) + -16
-21 + 1x = -12 + -16

Combine like terms: -12 + -16 = -28
-21 + 1x = -28

Solving
-21 + 1x = -28

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 1x = -28 + 21

Combine like terms: -21 + 21 = 0
0 + 1x = -28 + 21
1x = -28 + 21

Combine like terms: -28 + 21 = -7
1x = -7

Divide each side by '1'.
x = -7

Simplifying
x = -7

See similar equations:

| 4/9p-14=2 | | -5.73q=97.4 | | a(b+c)=ab+ac | | Y=p/m | | Y^9+2=-9 | | -3(2x+1)-6=9 | | 76+2x=228 | | 3x^2-4+1=0 | | P=rq+a | | 10-5x=2x+11 | | X-4=-5x+8 | | 23=6x-15 | | (16x^2)-40=0 | | 4s+9t=43 | | 36-(3c+4)=3(c+7)+c | | 2(x-4)=3x+11 | | W=mb-r | | 4x-3(2-3x)=4(x-4)-17 | | 5.05t=1.48t-3.57 | | -7/2r=-63/8 | | 2x+2y+3x+6y= | | 2(x-4)=2x+11 | | z+8=12-z | | Z=a-b+c | | 0=56x^2-72x+144 | | 16x^2-4x+252=0 | | 3/17=x/7 | | x=3-14 | | -2x=-54 | | (V+3)2=28 | | 4y-40=8y | | ((5Y^6)/(3Y^4))^(1/5) |

Equations solver categories